Evaluating meaningful levels of financial toxicity in gynecologic cancers. Issue 6 (15th April 2021) - Esselen, Katharine McKinley; Gompers, Annika; Hacker, Michele R; Bouberhan, Sara; Shea, Meghan; Summerlin, Sarah S; Rucker, Lindsay R; Huh, Warner K; Pisu, Maria; Liang, Margaret I
Abstract : Objective: The Comprehensive Score for Financial Toxicity (COST) is a validated instrument measuring the economic burden experienced by patients with cancer. We evaluated the frequency of financial toxicity at different COST levels and stratified risk factors and associations with cost-coping strategies by financial toxicity severity. Methods: We analyzed previously collected survey data of gynecologic oncology patients from two tertiary care institutions. Both surveys included the COST tool and questions assessing economic and behavioral cost-coping strategies. We adapted a proposed grading scale to define three groups: no/mild, moderate, and severe financial toxicity and used χ 2, Fisher's exact test, and Wilcoxon rank sum test to compare groups. We used Poisson regression to calculate crude and adjusted risk ratios for cost-coping strategies, comparing patients with moderate or severe to no/mild financial toxicity. Results: Among 308 patients, 14.9% had severe, 32.1% had moderate, and 52.9% had no/mild financial toxicity. Younger age, non-white race, lower education, unemployment, lower income, use of systemic therapy, and shorter time since diagnosis were associated with worse financial toxicity (all p<0.05). Respondents with moderate or severe financial toxicity were significantly more likely to use economic cost-coping strategies such as changing spending habits (adjusted risk ratio (aRR) 2.7, 95% CI 1.8 to 4.0 moderate; aRR 3.6, 95% CI 2.4 to 5.4 severe) and borrowing money (aRR 5.5, 95% CI 1.8 to 16.5 moderate; aRR 12.7, 95% CI 4.3 to 37.1 severe). Those with severe financial toxicity also had a significantly higher risk of behavioral cost-coping through medication non-compliance (aRR 4.6, 95% CI 1.2 to 18.1). Conclusions: Among a geographically diverse cohort of gynecologic oncology patients, nearly half reported financial toxicity (COST <26), which was associated with economic cost-coping strategies. In those 14.9% of patients reporting severe financial toxicity (COST <14) there was also an increased risk of medication non-compliance, which may lead to worse health outcomes in this group.